Gut Microbial Dysbiosis Is Associated With Profibrotic Factors in Liver Fibrosis Mice - Wan, Sizhe; Nie, Yuan; Zhang, Yue; Huang, Chenkai; Zhu, Xuan (Frontiers in Cellular and Infection Microbiology, 2020)
Liver fibrosis is the result of repair and scar formation after stimulation of the liver by injury factors. Profibrotic factors NOX4 and RhoA participate in the activation of hepatic stellate cells (HSCs) and accelerate the development of liver fibrosis. Abnormal intrahepatic metabolism during liver fibrosis interferes with intestinal homeostasis through the liver–gut axis. We investigated the changes in intestinal microbiota diversity, abundance, and functional prediction during liver fibrosis and the correlation of these changes with NOX4 and RhoA intervention based on high-throughput 16S sequencing. In liver fibrosis mice, the diversity and abundance of the intestinal microbiota decreased, the composition of the microbiota was disordered, the potentially beneficial bacteria Firmicutes and Lactobacillus decreased, and the functional prediction also changed compared with normal mice. However, in the liver fibrosis mice with NOX4 or RhoA intervention, these disorders showed a certain degree of improvement. In conclusion, the intestinal microbiota is disordered during liver fibrosis, and the disorder is related to NOX4 and RhoA. This study provides theoretical support for a better understanding of the underlying mechanisms of liver fibrosis development and the development of diagnostic and therapeutic technologies for liver fibrosis treatment based on the intestinal microbiota.